Use of Cost-Benefit Analysis in Capital Budgeting Optimization in Public Sector - Rizky Tiaro Sulistyo; Yolinda Aprillia (IPSAR (International Public Sector Accounting Review), 2023)
As a public servant, the government has obligations and responsibilities to use every available resource effectively and efficiently. Therefore, using a capital budget is necessary to measure the extent to which the costs incurred can support the expected outputs and results. One of the methods that can be chosen in applying capital budgeting in the public sector is Cost-Benefit Analysis. This method will measure whether the results (benefits) obtained exceed the resources (costs) incurred. This paper aims to identify the use of the Cost-Benefit Analysis method in the public sector and the optimization of capital budgeting through its use. The results of the study indicate that there are several government programs and activities that apply the Cost-Benefit Analysis method in their implementation. Furthermore, it was also found that optimization resulted from implementing capital budgeting in the public sector.